2001
DOI: 10.1024/0300-9831.71.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Folate, Antioxidant Vitamins and other Constituents in Fruit and Vegetables in the Prevention of Cardiovascular Disease: The Epidemiological Evidence

Abstract: Evidence that fruit and vegetables may protect against coronary heart disease is accumulating. It is unclear which constituents of fruit and vegetables are responsible for this protective effect. Folate as a co-substrate in homocysteine metabolism may be important. An intake of about 400 micrograms folate equivalents/day seems to be required to achieve stable low homocysteine blood levels. Five of eight epidemiologic studies show significant inverse associations between folate and cardiovascular disease. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 83 publications
0
42
0
Order By: Relevance
“…Fruit and vegetables are rich sources of micronutrients and bioactive phytochemicals that may play an important role in the prevention of CHD and stroke and are relatively low in energy density (28) . We found that more variety in fruit and vegetables was associated with higher intakes of vitamin C, carotenoids, flavonoids and dietary fibre.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit and vegetables are rich sources of micronutrients and bioactive phytochemicals that may play an important role in the prevention of CHD and stroke and are relatively low in energy density (28) . We found that more variety in fruit and vegetables was associated with higher intakes of vitamin C, carotenoids, flavonoids and dietary fibre.…”
Section: Discussionmentioning
confidence: 99%
“…Some strawberry cultivars have the highest concentrations of L-ascorbic acid among all fruits (Haffner and Vestrheim, 1997). Other phenolic compounds belonging to distinct chemical classes, many of which are also potential antioxidants and anticancer agents (Eichholzer et al, 2001;Schieber et al, 2001), have been isolated from rosaceous fruits (Macheix et al, 1991).…”
mentioning
confidence: 99%
“…The intake of antioxidant vitamins not as supplements, but within a healthy diet, reduces CVD risks (Eichholzer et al 2001, Obrenovich et al 2011. Despite controversies, there is evidence that antioxidant vitamins may inhibit LDL oxidation to its more atherogenic form, therefore preserving the inhibition of atherosclerotic plaque formation ASSOCIATION BETWEEN CARDIOVASCULAR RISk FACTORS AND DNA DAMAGE (Wattanapitayakul and Bauer 2001).…”
Section: Discussionmentioning
confidence: 99%